2020
DOI: 10.21203/rs.3.rs-110947/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic profiling of neocortical tissue discriminates Alzheimer’s disease from mild cognitive impairment, high pathology controls, and normal controls

Abstract: Background Alzheimer’s disease (AD) is the most common cause of dementia, accounting for an estimated 60 to 80% of cases, and is the sixth-leading cause of death in the United States. While considerable advancements have been made in the clinical care of AD, it remains a complicated disorder that can be difficult to identify definitively in its earliest stages. Recently, mass spectrometry (MS)-based metabolomics has shown significant potential for elucidation of disease mechanisms and identification of therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The targeted LC-MS/MS method used here was modeled after that developed and used in a growing number of studies [71][72][73] . Briefly, all LC-MS/MS experiments were performed on an Agilent 1290 UPLC-6490 QQQ-MS system.…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…The targeted LC-MS/MS method used here was modeled after that developed and used in a growing number of studies [71][72][73] . Briefly, all LC-MS/MS experiments were performed on an Agilent 1290 UPLC-6490 QQQ-MS system.…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…The targeted LC-MS/MS method in this study was modeled after that developed and used in a growing number of studies extracting a detailed list of confirmed metabolites (Jasbi et al, 2021; Shi et al, 2019; Zhu et al, 2015). Briefly, we included ∼300 metabolites (additional information available from the authors by request) selected from >35 metabolic pathways of biological significance to energy expenditure (such as glycolysis, TCA cycle, purine metabolism, and amino acid metabolism).…”
Section: Methodsmentioning
confidence: 99%
“…The targeted LC-MS/MS method used here was modeled after that developed and used in a growing number of studies (Bapat et al 2021;Jasbi, Baker, et al 2019;Jasbi et al 2021;Jasbi, Mitchell, et al 2019;Wang et al 2019). Briefly, all LC-MS/MS experiments were performed on an Agilent 1290 UPLC-6490 QQQ-MS system.…”
Section: Metabolomicsmentioning
confidence: 99%